2019
DOI: 10.4236/ojpsych.2019.92014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pattern of Alcohol Use among Adults in an Urban Slum in South East Nigeria

Abstract: Background: Alcohol is one of the most commonly abused psychoactive substances in the country. Studies have shown sharp increases in alcohol consumption among Nigerians. This increase is likely to continue because of increased local production and availability of alcohol in the country. Knowledge of the prevalence and pattern of current alcohol use is important considering the public health and socioeconomic effects of alcohol use. Methods: Using a semi-structured questionnaire, we estimated the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
3
6
2
Order By: Relevance
“…The magnitude of current alcohol use in this study was 8.24%. The finding is lower than studies conducted in Ethiopia 13.9% ( 18 ), Gondar 23.7% ( 17 ), Mekelle 25.1% ( 43 ), South Ethiopia 22.4% ( 54 ), Kenya 12.8% ( 55 ), South Africa 20% ( 56 ), and Nigeria 66.7% ( 57 ). The possible reason for the discrepancy might be due to the tools used to assess the current alcohol use.…”
Section: Discussioncontrasting
confidence: 59%
“…The magnitude of current alcohol use in this study was 8.24%. The finding is lower than studies conducted in Ethiopia 13.9% ( 18 ), Gondar 23.7% ( 17 ), Mekelle 25.1% ( 43 ), South Ethiopia 22.4% ( 54 ), Kenya 12.8% ( 55 ), South Africa 20% ( 56 ), and Nigeria 66.7% ( 57 ). The possible reason for the discrepancy might be due to the tools used to assess the current alcohol use.…”
Section: Discussioncontrasting
confidence: 59%
“…Alcohol use was found to be increasing with increasing level of education in this study, in contrast to studies by Rosoff et al [3] and Onodugo OD et al [4].…”
Section: Discussioncontrasting
confidence: 99%
“…Levels of education seem to have a direct effect on the behavioral risk and socio economic status. Some studies have shown some association between cardiovascular risks and levels of education-association between alcohol and increasing levels of education [3] [4], meat consumption and increasing levels of education [5] [6], type 2 Diabetes mellitus and lower levels of education [7], long working hours and increasing levels of education [8], obesity and lower levels of education [9], hypertension, short nighttime sleep duration and different levels of education [10] [11]. There was a paucity of studies on the influence of educational levels on cardiovascular disease risks in Nigeria, prompting this study which was set out to evaluate these associations.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in an urban slum in South-eastern Nigeria found that only 8.1% of the people drank alcohol above the general recommended unit per week. Alcohol consumption was supposed to be higher in urban slums compared to rural settings and organized urban dwellings [46]. This prevalence of alcohol consumption in Nigeria is far lower than what is obtainable in most cold climes.…”
Section: Association Between Alcohol Use and Erectile Dysfunction In Subjects With Type 2 Diabetes Mellitusmentioning
confidence: 93%